2019
DOI: 10.3390/molecules24050871
|View full text |Cite
|
Sign up to set email alerts
|

Sterile and Dual-Porous Aerogels Scaffolds Obtained through a Multistep Supercritical CO2-Based Approach

Abstract: Aerogels from natural polymers are endowed with attractive textural and biological properties for biomedical applications due to their high open mesoporosity, low density, and reduced toxicity. Nevertheless, the lack of macroporosity in the aerogel structure and of a sterilization method suitable for these materials restrict their use for regenerative medicine purposes and prompt the research on getting ready-to-implant dual (macro + meso)porous aerogels. In this work, zein, a family of proteins present in mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 64 publications
0
27
0
Order By: Relevance
“…Biopolymers as renewable resources are of particular interest for biomedical and environmental applications due to their compatibility with living tissue (biocompatibility) and bio-degradability [18,21,40]. In this context, it has been demonstrated that abundant natural polymers like cellulose, starch or pectin can be transformed into high value-added gels and aerogels that have been promisingly tested as cell scaffolding materials, artificial cartilage, blood vessels or for efficient adsorption of noble metals (recycling) or pollutants of aqueous systems (e.g., heavy metals, oil, organic compounds) [25,41,42,43]. A significant advantage of bio-based aerogels over their synthetic polymer-based counterparts is that no toxic compound is involved in their preparation.…”
Section: Current Status On Aerogels For Biomedical and Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Biopolymers as renewable resources are of particular interest for biomedical and environmental applications due to their compatibility with living tissue (biocompatibility) and bio-degradability [18,21,40]. In this context, it has been demonstrated that abundant natural polymers like cellulose, starch or pectin can be transformed into high value-added gels and aerogels that have been promisingly tested as cell scaffolding materials, artificial cartilage, blood vessels or for efficient adsorption of noble metals (recycling) or pollutants of aqueous systems (e.g., heavy metals, oil, organic compounds) [25,41,42,43]. A significant advantage of bio-based aerogels over their synthetic polymer-based counterparts is that no toxic compound is involved in their preparation.…”
Section: Current Status On Aerogels For Biomedical and Environmentmentioning
confidence: 99%
“…For regenerative medicine and plastic surgery, aerogel-based scaffolds have a nanostructure that can mimic the extracellular matrix of the natural tissue and aerogel-containing scaffolds lead to materials with improved roughness and pore interconnectivity of interest for tissue integration [8,16,41,51,67,68,69,70,71]. For example, cellulose phosphate of low degree of substitution has been demonstrated to be a good source for such cell scaffolding materials since it allows robust growth of mesenchymal stem cells, osteogenic differentiation, formation of hydroxyapatite layer in simulated body fluid, is hemocompatible and does not show an inflammatory response on the alternative pathway [72].…”
Section: Current Status On Aerogels For Biomedical and Environmentmentioning
confidence: 99%
“…These properties of aerogels have been exploited, particularly for silica aerogels, in the development of thermal insulation systems and Cherenkov detectors for construction and aerospace industries. The advent of novel aerogel sources from natural polymers (e.g., polysaccharides, proteins) and the development of hybrid aerogels have extended the possibilities of these materials for new applications and fields like biomedical and environmental applications [2,4,5,6]. Gel source (chemical structure, molecular weight, concentration) and chemical modifications of gels (co-gelation, post-gelation) strongly influence the textural properties of the resulting aerogels as well as the choice of the drying method.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of melamine-formaldehyde improved the compression strength of starch-based aerogels as compared with melamine-formaldehyde aerogels [374]. Incorporation of zein to corn starch improved the Young's modulus compared to neat corn starch-based aerogels [371].…”
Section: Aerogels From Starchmentioning
confidence: 96%